(untitled) (The Pretoria Student Law Review, 2021)
The call for decolonisation of legal education stems from the acknowledgement of the presence of retrogressive colonial approach to legal education. This approach includes a neutral and formal teaching that is blinded to ethical and social considerations. Law is a mirror of a country`s moral, cultural and social values and yet South African legal education distances itself with all other considerations and insists on a Western, autonomous and functionalist approach to legal education. This results in the moulding of uncritical and thoughtless “modern lawyers” with no concern to ethics and justice. Decolonisation demands a critical legal education and the replacement of the colonial “Black letter” teaching for a therapeutic jurisprudence. Both of which demand an interdisciplinary approach to legal education that acknowledges the impact of legal education on politics, society and culture. Thus, this article uses Critical Legal Studies (CLS) to deconstruct the colonial legal education epistemology.